Predictive control strategy for a novel 15-level inverter with reduced power components - Taoufiq El Ansari; Ayoub El Gadari; Youssef Ounejjar (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This paper proposes a novel fifteen-level H-PTC inverter topology controlled by model predictive control (MPC), which reduces the number of components. The design employs only two DC sources, nine switches, including one bidirectional switch, and a single capacitor. The system’s performance is validated through MATLAB/Simulink simulations under various scenarios, such as steady-state operation, load variations, nonlinear loads, and sudden supply voltage disturbances. Compared to existing topologies, the proposed inverter demonstrates hardware simplicity, high output quality, and enhanced dynamic robustness. Notably, it features very low total standing voltage (TSV) and a minimized cost function value of 2.05. For a load characterized by R = 20 Ω and L = 20 mH, the total harmonic distortion (THD) of the load current is 0.88%, confirming excellent power quality without the need for output filters. The MPC controller ensures a fast dynamic response and strong adaptability, making this topology ideal for modern energy conversion applications.